PENGARUH METODE BERMAIN PERAN TERHADAP AKTUALISASI DIRI SISWA KRISTEN PADA MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN DI SEKOLAH DASAR BOPKRI WONOSARI - KRISNAWATI, DWI; WENING, SRI (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2024)
Elementary school students are in a period of social growth and development and need encouragement from teachers to dare to self-actualize. Student self-actualization is a form of self-development that requires awareness from each student to function learning activities as a means of developing potential. The teacher's skills in communicating learning material through the role-playing method will help students to respond actively to the learning material. The role-playing method can create interesting and interactive learning that is student-centered. So that it influences students to self-actualize in the form of students' self-confidence, ability to use emotions, social skills, self-acceptance, creativity, and learning to solve problems, developing imagination and courage in carrying out their learning responsibilities independently. In this way, learning objectives will be achieved maximally, which is marked by students' courage to actualize them. With the role playing method, students' self-actualization will be achieved, that is, students will be able to recognize their own abilities which can be developed by involving themselves in every learning activity and social relationships with other students. Students have good self-confidence, students have the ability to use emotions appropriately, students have social skills, self-acceptance, creativity, and learn to solve problems. This research aims to test the hypothesis which states that there is a significant influence of the role playing method on the self-actualization of Christian students in Christian Religious Education subjects at the Bopkri Wonosari Elementary School. By using quantitative descriptive research methods and SPSS 16.0 data processing, there are significant results for self-actualization in elementary school students at Bopkri Wonosari. ABSTRAKSiswa Sekolah Dasar sedang dalam masa pertumbuhan dan perkembangan sosial membutuhkan dorongan dari guru untuk berani beraktualisasi diri. Aktualisasi diri siswa merupakan wujud pengembangkan diri yang membutuhkan kesadaran dari setiap siswa untuk memfungsikan kegiatan pembelajaran sebagai sarana dalam mengembangkan potensi. Ketrampilan guru dalam mengkomunikasikan materi pembelajaran melalui metode bermain peran akan menolong siswa untuk merespon aktif materi pembelajaran. Dengan Metode bermain peran dapat menciptakan pembelajaran yang menarik dan interaktif yang berpusat pada siswa. Sehingga mempengaruhi siswa untuk beraktualisasi diri dalam bentuk kepercayaan diri siswa, kemampuan menggunakan emosi, kemampuan sosial, penerimaan diri, kreatifitas, dan belajar memecahkan masalah, mengembangkan daya imajinasi serta keberanian dalam melakukan tanggungjawab belajarnya secara mandiri. Dengan demikian tujuan pembelajaran akan tercapai dengan maksimal yang di tandai dengan keberanian siswa untuk beraktualisai. Dengan metode bermain peran maka akan tercapai aktualisasi diri siswa yaitu siswa mampu mengenal kemampuan dirinya yang dapat dikembangkan dengan melibatkan diri dalam setiap aktifitas pembelajaran maupun hubungan sosial dengan siswa lain. Siswa menjadi memiliki kepercayaan diri yang baik, siswa memiliki kemampuan menggunakan emosi dengan tepat, siswa memiliki kemampuan sosial, penerimaan diri, kreatifitas, dan belajar memecahkan masalah. Penelitian ini memiliki tujuan menguji hipotesis yang berbunyi terdapat pengaruh metode bermain peran yang signifikan terhadap aktualisasi diri siswa kristen pada mata pelajaran Pendidikan Agama Kristen di Sekolah Dasar Bopkri Wonosari. Dengan menggunakan metode penelitian Deskriptif kuantitatif dan pengolahan data SPSS 16.0 dengan demikian terdapat hasil yang signifikan terhadap aktualisasi diri pada siswa SD Bopkri Wonosari.